12 Professionals', patients', and families' views on the use of opioids for breathlessness: a rapid systematic review using the framework method and pillar process. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Reedy, Florence; Pearson, Mark; Johnson, Miriam; Clark, Joseph; Greenley, Sarah; Currow, David
Abstract : Background: In combination with disease-modifying therapies and non-pharmacological interventions, opioids can safely reduce breathlessness in patients with severe illness. However, implementation in clinical practice varies. Methods: Three electronic databases (MEDLINE and Embase via OVID and ASSIA via Proquest) were searched (March 2020) using a predefined search strategy. Studies were also citation chained from key papers in the field. Reviewers FR and JC double-screened titles and abstracts of papers against the a priori eligibility criteria. FR independently read and extracted data from included studies using the five-stage framework synthesis method: familiarization, framework selection, indexing, charting and mapping. FR then used the pillar process to synthesise qualitative and quantitative data in four stages: listing, matching, checking and pillar building. Reviewers FR, JC and MP critically appraised included studies using the MMAT. Results: 843 papers were identified from database searches and citation chaining after de-duplication. Following screening 22 studies were included in the synthesis. Five themes were developed which comprise of both barriers and enablers to opioid use for breathlessness: i) clinician/patient background, ii) education/knowledge/experience, iii) relationship between clinician/family, iv) clinician/patient fear of opioids and v) regulatory issues. The review highlights significant barriers and enablers to the use of opioids for the symptomatic treatment of breathlessness based on the knowledge, views and attitudes of clinicians, patients and families. The review shows clinicians' interactions with patients and their families strongly influences concordance with opioid treatment regimens for breathlessness. Conclusions: As clinicians', patients', and families' knowledge about the delicate balance between opioid benefits and risks is generally poor, education is likely to be a necessary but not sufficient factor for improving the implementation of opioids for breathlessness. Further research ought to address ways of improving clinician, patient and family therapeutic relationships and improving knowledge on opioid use for breathlessness.